2013
DOI: 10.1177/0954411913501294
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hydration on the frequency-dependent viscoelastic properties of articular cartilage

Abstract: The aim of this study was to determine the effect of tissue hydration on the frequency-dependant viscoelastic properties of articular cartilage. Such changes were determined at frequencies associated with normal (1-10 Hz) and impulsive/traumatic (90 Hz) heel-strike times. Cartilage on bone samples, obtained from bovine humeral heads, was tested when hypo-hydrated and hyper-hydrated using dynamic mechanical analysis. Dynamic mechanical analysis was performed at a range of frequencies between 1 and 90 Hz. Hypo-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
48
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(60 citation statements)
references
References 36 publications
12
48
0
Order By: Relevance
“…Crack length was found to increase with increasing loading frequency; this increase was also found to be greater at higher maximum loads. An increase in cartilage damage with increasing the loading frequency was predicted in previous studies 12,14,28 . This prediction was made because of the change in viscoelastic properties of articular cartilage with frequency.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Crack length was found to increase with increasing loading frequency; this increase was also found to be greater at higher maximum loads. An increase in cartilage damage with increasing the loading frequency was predicted in previous studies 12,14,28 . This prediction was made because of the change in viscoelastic properties of articular cartilage with frequency.…”
Section: Discussionsupporting
confidence: 67%
“…Significant increase in crack length with frequency in peak stresses which resembles peak stresses acting on cartilage during light and moderate activities shows the important role of loading frequency in the initiation and propagation of damage on the surface of articular cartilage in this study. Other studies 12,13,28 have reported that the ability of cartilage to store and dissipate energy is altered with loading frequency. This may change the stress transfer to the underlying bone which leads to bone stiffening and ultimately failure of articular cartilage 13 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Investigations into the biomechanical properties of soft tissues have supported this notion, with behaviour linked with extracellular matrix (ECM) hydration both in vivo and in vitro (39). The viscoelastic properties of articular cartilage for example, have been shown to alter depending on hydration, with reduced ability to dissipate energy and resultant increased likelihood of rupture in a hyperhydrated state (as in osteoarthritis) (40). At the cellular level, the properties of elastin have shown significant stiffening with dehydration, resulting in reduced fatigue resistance to cyclic loading particularly at high frequency (39).…”
Section: Hydration Of Tissues and Cellsmentioning
confidence: 99%
“…The bouncing corresponds to elastic behavior on a short time scale, while the flattening corresponds to viscous flow on a long time scale. Along with fat, a myriad of other biological tissues are viscoelastic, including cartilage, ligaments, tendons, and muscle (1315). …”
Section: Discussionmentioning
confidence: 99%